2020
DOI: 10.1016/j.ijcha.2020.100599
|View full text |Cite
|
Sign up to set email alerts
|

History of cigarette smoking and heart transplant outcomes

Abstract: Background : Active cigarette smoking (CS) is a contraindication for Orthotopic Heart Transplantation (OHT) with a recommendation that HT candidates be free from CS for at minimum 6 months prior to HT. Animal studies have shown that a history of CS is associated with increased risk of allograft rejection, but few studies have examined the association of past CS and HT outcomes. Methods : Data were analyzed from HT recipients captured in the United Net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…One review study found 16% of heart failure patients continue to smoke after diagnosis, and that persistent smoking not only leads to increased mortality, as we saw in our study, but is also associated with increased risk of readmissions, poor health status, ventricular tachycardia, and arterial stiffness [9]. It is also problematic that among those with a history of smoking who are able to receive a heart transplant have a high risk of poor outcomes post-heart transplantation [55]. One study found 26% of current and former smokers who all stopped prior to heart transplantation resumed smoking after transplantation [56].…”
Section: Discussionsupporting
confidence: 53%
“…One review study found 16% of heart failure patients continue to smoke after diagnosis, and that persistent smoking not only leads to increased mortality, as we saw in our study, but is also associated with increased risk of readmissions, poor health status, ventricular tachycardia, and arterial stiffness [9]. It is also problematic that among those with a history of smoking who are able to receive a heart transplant have a high risk of poor outcomes post-heart transplantation [55]. One study found 26% of current and former smokers who all stopped prior to heart transplantation resumed smoking after transplantation [56].…”
Section: Discussionsupporting
confidence: 53%
“…HTR with a history of smoking have a higher risk of posttransplant mortality, malignancy, graft failure and hospitalizations for acute rejection and infection. An observational study conducted in the USA found that patients who consumed tobacco in the 12 months preceding transplantation were at a higher risk of mortality and graft failure among others [77]. Therefore, it is important to encourage patients to quit smoking by promoting programmes that motivate its cessation.…”
Section: Tobaccomentioning
confidence: 99%
“…Tobacco exposure and smoking increase the risk of cardiovascular events such as coronary disease or thrombotic events by a variety of mechanisms: platelet dysfunction, altered endothelial function, oxidative processes, inflammation and lipid oxidation [77,78].…”
Section: Tobaccomentioning
confidence: 99%
“…Graft survival was decreased in the both group of donors and recipients which were exposed to tobacco smoke. [58][59][60] Furthermore, exposure to smoke was associated with increased systemic inflammatory cytokine, hospitalization of infection and mortality. 58,59 Posttransplant smoking in lung transplant patients was associated with declined of pulmonary function, but the study failed to demonstrate association of cigarette smoke and graft rejection.…”
Section: Smoking and Organ Transplantationmentioning
confidence: 99%
“…[58][59][60] Furthermore, exposure to smoke was associated with increased systemic inflammatory cytokine, hospitalization of infection and mortality. 58,59 Posttransplant smoking in lung transplant patients was associated with declined of pulmonary function, but the study failed to demonstrate association of cigarette smoke and graft rejection. 61 In kidney transplantation, cigarette smoking was associated with decreased graft survival especially smoking at time of tranpslantaion, [62][63][64] hospitalization of infection, and death-censored graft failure.…”
Section: Smoking and Organ Transplantationmentioning
confidence: 99%